# simplify by combining like terms:

x sqrt(18) - 3 sqrt(8x)sqrd

If <sqrt(8x)sqrd> means [sqrt(8x)]^2, then that also equals 8x. So
x sqrt(18) - 3 sqrt(8x)sqrd
= x[sqrt(9*2)-3*8]
= 3x(sqrt 2 -3

## To simplify the expression x sqrt(18) - 3 sqrt(8x)sqrd, you can start by simplifying the square root terms:

sqrt(18) = sqrt(9 * 2) = sqrt(9) * sqrt(2) = 3 sqrt(2)

Next, simplify the square root squared term:

sqrt(8x)^2 = (sqrt(8x))^2 = 8x

Now, you can rewrite the expression as:

x sqrt(18) - 3 sqrt(8x)sqrd = x (3 sqrt(2)) - 3 (8x)

= 3x sqrt(2) - 24x

So, the simplified expression is 3x sqrt(2) - 24x.

## To simplify the given expression by combining like terms, let's first simplify the square roots.

The square root of 18 can be simplified as the square root of 9 times the square root of 2. Since the square root of 9 is equal to 3, we can rewrite the expression as:

x * sqrt(9 * 2) - 3 * sqrt(8x)^2

Simplifying further, we have:

x * (3 * sqrt(2)) - 3 * (sqrt(8x))^2

The square of sqrt(8x) simplifies to 8x:

x * (3 * sqrt(2)) - 3 * 8x

Now, combining like terms, we have:

3x * sqrt(2) - 24x

Therefore, the simplified expression is:

3x * sqrt(2) - 24x